2022
DOI: 10.1177/03635465221084365
|View full text |Cite
|
Sign up to set email alerts
|

One in Three Patients With Chronic Lateral Ankle Instability Has a Cartilage Lesion

Abstract: Background: Chronic lateral ankle instability (CLAI) is associated with the presence or development of intra-articular pathologies such as chondral or osteochondral lesions, or (O)CLs. Currently, the incidence of (O)CLs in patients with CLAI is unknown. Purpose: To determine the incidence of (O)CLs in patients with CLAI. Study Design: Systematic review and meta-analysis; Level of evidence, 4. Methods: A literature search was conducted in the PubMed (MEDLINE), Embase (Ovid), and Cochrane databases for articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…These findings were in agreement with our previous findings and those of several ankle studies that reported a T2/T2* increase in the talocrural cartilage of patients with CLAI, again with stronger effects in the medial joint regions, which has been proven in arthroscopic and cadaveric studies. 9,15 In the meta-analysis by Wijnhoud et al, 23 an overall 85% of osteochondral lesions in patients with CLAI were talar lesions; of the 2 studies that examined tibial lesions, 17% of osteochondral lesions were on the distal tibia. This finding could be explained by previous kinematic studies that reported increased stress distributions and reduced tibiotalar contact area in the medial compartment of the talus when the lateral ligaments were released.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were in agreement with our previous findings and those of several ankle studies that reported a T2/T2* increase in the talocrural cartilage of patients with CLAI, again with stronger effects in the medial joint regions, which has been proven in arthroscopic and cadaveric studies. 9,15 In the meta-analysis by Wijnhoud et al, 23 an overall 85% of osteochondral lesions in patients with CLAI were talar lesions; of the 2 studies that examined tibial lesions, 17% of osteochondral lesions were on the distal tibia. This finding could be explained by previous kinematic studies that reported increased stress distributions and reduced tibiotalar contact area in the medial compartment of the talus when the lateral ligaments were released.…”
Section: Discussionmentioning
confidence: 99%
“… 15 According to a recent systematic review, 32% of patients with CLAI have chondral or osteochondral lesions. 42 Gradual cartilage degradation causes progression of the vicious cascade from a focal cartilage lesion toward osteoarthritis. 11 Based on the results of the present study, the incidence of undiagnosed ILAL was 35.8% (38/106).…”
Section: Discussionmentioning
confidence: 99%
“… Clinical evaluation, including patient history and physical examination is performed for all patients at the outpatient clinic in order to assess symptoms befitting an OLT. Additionally, care is taken to assess any relevant coexisting pathologies of the foot and ankle which may warrant treatment, such as symptomatic ankle instability which is frequently encountered in patients with OLT [ 1 , 22 ]. Radiological assessment of the lesion is preferably carried out through a preoperative computed tomography (CT) scan to assess the three-dimensional lesion and fragment size, lesion location, as well as the lesion and fragment morphology.…”
Section: Surgical Principles and Objectivementioning
confidence: 99%
“…Clinical evaluation, including patient history and physical examination is performed for all patients at the outpatient clinic in order to assess symptoms befitting an OLT. Additionally, care is taken to assess any relevant coexisting pathologies of the foot and ankle which may warrant treatment, such as symptomatic ankle instability which is frequently encountered in patients with OLT [ 1 , 22 ].…”
Section: Surgical Principles and Objectivementioning
confidence: 99%